DETERMINANT OF FREE CASH FLOW, LIFE CYCLE, FIRM SIZE, LEVERAGE, ASSETS GROWTH AND INVESTMENT OPPORTUNITY SET ON DIVIDEND OF MANUFACTURING COMPANIES THAT LISTED IN INDONESIA STOCK EXCHANGE - Fitratama, Venu B1024161005 (Jurnal Manajemen Update, 2020)
Company decision to give profits to their investors is involved by many things including dividend policy of company itself. Therefore, this study discusses the effects of free cash flow, life cycle, firm size, leverage, assets growth and investment opportunity set on dividend of manufacturing companies that listed in indonesia stock exchange. Dependent variable used is dividend payout ratio. Independent variables used are free cash flow, life cycle, firm size, leverage, assets growth, and investment opportunity set.The population in this study is manufacturing company listed on Indonesia Stock Exchange (BEI) in the period of 2015 - 2018. The sample collected using purposive sampling methods. Total of 28 companies were determined as samples. Method of analysis in this study is using panel data regression with basis on fixed effect model.The result of this study indicates that independent variables of free cash flow, life cycle, firm size, leverage, and investment opportunity set have positive impact toward dividend payout ratio while assets growth has negative impact on dividend payout ratio. The result of determination coefficient shows that the independent variables give affect 63.69% against dependent variable.Ahmad, R. (2009). Pengaruh Invesment Opportunity Set (IOS) Terhadap Kebijakan Dividen dengan Pemoderasi Pilihan Prosedur Akuntansi Pada Perusahaan yang Go Public di bursa Efek Jakarta. Jurnal Bisnis dan Manajemen. Vol. 5, No. 1.Anthony, J. H., & Ramesh, K. (1992). Association Between Accounting Performance Measures and Stock Prices: A Test of The Life Cycle Hypothesis. Journal of Accounting and Economics, 203-227.Brigham, E. F., & Houston, J. F. (2007). Fundamentals of Financial Management 11th Edition. South-Wester.DeAngelo, H., & DeAngelo, L. (2006). The Irrelevance of the MM Dividend Irrelevance Theorem. Journal of Financial Economics, 293-316.DeAngelo, H., DeAngelo, L., & Stulz, R. M. (2006). Dividend Policy and the Earned/ Contributed Capital Mix: A Test of the Lifecycle Theory. Journal of Financial Economics, 227-254.Denis, D. J., & Osobov, I. (2008). Why Do Firms Pay Dividends? International Evidence on the Determinants of Dividend Policy. Journal of Financial Economics, 62-82.Fajriah, N. (2011). Analisis Pengaruh ROE, DER, Manajemen Ownership, Free Cash Flow, dan Size Terhadap Dividend Payout Ratio Pada Perusahaan-perusahaan Manufaktur Yang Terdaftar di Bursa Efek Indonesia (BEI) Tahun 2006-2009. Skripsi Fakultas Ekonomi Universitas Diponegoro.Giriati. (2015). Free Cash Flow, Dividend Policy, Investment Opportunity Set, Opportunistic Behaviour and Firm's Value (A Study About Agency Theory). 3rd Global Conference on Business and Social Science.Gustiana, N. (2009). Pengaruh Insider Ownership, Dispersion of Ownership, Free Cash Flow, Collaterizable Assets dan Tingkat Pertumbuhan Terhadap Dividend Payout Ratio Pada Perusahaan- Perusahaan Manufaktur di Bursa Efek Indonesia Tahun 2004- 2008.Holder, M., Langrehr, F., & Hexter, J. (1998). Dividend Policy Determinants: An Investigation of the Influences of Stakeholder Theory. Financial management 27, 73-80.Keown, A. J. (2003). Financial Management : Principles and Applications 10th ed. New Jersey: Prentice Hall.Kieso, D. E., & Weygandt, J. J. (2001). Financial Management: Principles and Applications 10th Edition. New York: John Willey & Sons, Inc.Lestari, J. S. (2012). Determinants of Dividend Decision: Evidence From the Indonesia Stock Exchange. Integr. Bus. Econ. Res., 1(1) 346.Levy, H., & Sarnat, M. (1990). Capital Investment and Financial Decision 4th ed. New York: Prentice Hall.Mahadwartha, P. A. (2007). The Association of Managerial Ownership with Dividend Policy and Leverage Policy: Indonesian Firm. SSRN Working Papers Series.Miller, D., & Friesen, P. H. (1984). A Longitudinal Study of the Corporate Life Cycle. Management Science, 30: 1161-1183.Miller, M. H., & Modigliani, F. (1961). Dividend Policy, Growth and the Valuation of Shares. The Journal of Business, Vol. 34 No. 4, pp. 411-433.Mollah, A. S., Keasey, K., & Short, H. (2002). The Influence of Agency Costs on Dividend Policy in An Emerging Market: Evidence from the Dhaka Stock Exchange. Working Paper, Leeds University Business School.Murhadi, W. (2008). Studi Kebijakan DIviden: Anteseden dan Dampaknya terhadap Harga Saham. Manajemen dan Kewirausahaan, 10.Myers, S. C., & Majluf, N. S. (1984). Corporate Financing and Investment Decision When Firms Have Information That Investor Do Not Have. Journal of Financial Economics 13, 187-221.Puspita, F. (2009). Anallisis Faktor- Faktor yang Mempengaruhi Kebijakan Dividend Payout Ratio (Studi Kasus pada Perusahaan Yang Terdaftar di Bursa Efek Indonesia Periode 2005-2007).Riyanto, B. (n.d.). Dasar-dasar Pembelanjaan Perusahaan. Yogyakarta: BPFE, 2001.Rosdini, D. (2009). Pengaruh Free Cash Flow terhadap Dividend Payout Ratio. Working paper in Accounting and Finance.Suharli, M., & Rachpriliani, A. (2006). Studi Empiris Faktor yang Berpengaruh terhadap Ketepatan Waktu Pelaporan Keuangan. Jurnal Bisnis dan Akuntansi, Vol.8 No.1 (April): 34-55.Thanatawee, Y. (2011). Life-Cycle theory and Free Cash Flow Hypothesis: Evidence from Dividend Policy in Thailand. International Journal of Financial Research 2.Yan, Z. (2010). A New Methodology of Measuring Corporate Life-Cycle Stage. SSRN Electronic Journal.